Strategies to reduce uric acid through gut microbiota intervention - Cui, Yueying; An, Peiyu; Li, Feng; Duan, Fengsen; Mei, Zusong; Ye, Qiao; Wang, Guangyun; Zhang, Haitao; Luo, Yuan (Frontiers in Microbiology, 2025)
Hyperuricaemia (HUA) is a metabolic disorder resulting from the dysregulation of purine metabolism. It is closely associated with gout and various metabolic syndromes, representing an increasing global public health challenge. Current treatment approaches for HUA and gout generally involve the lifelong administration of urate-lowering agents to maintain optimal serum urate concentrations. However, poor patient adherence, often due to potential hepatorenal toxicity, frequently leads to disease relapse. Recent evidence indicates that the gut microbiota plays a significant role in maintaining urate homeostasis through multiple mechanisms, including the modulation of purine metabolism, urate catabolism and excretion, regulation of inflammatory responses, and preservation of intestinal barrier integrity. These findings highlight the gut microbiota as a promising novel therapeutic target. This review synthesizes recent progress in three key areas: (1) the relationship between the gut microbiota and HUA; (2) microbial mechanisms underlying urate-lowering effects, such as microbial purine and urate metabolism, regulation of urate transporters like ABCG2, and production of anti-inflammatory metabolites; and (3) microbiota-based therapeutic interventions, including probiotics, engineered bacterial strains, fecal microbiota transplantation, and pharmabiotic strategies. Additionally, we explore the translational potential of microbiota modulation in clinical settings and outline directions for future research. By integrating mechanistic understanding with therapeutic innovation, this review offers researchers and clinicians a comprehensive framework for advancing microbiota-targeted approaches in the management of hyperuricaemia.